2020
DOI: 10.1159/000511325
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Findings in 32 Patients with COVID-19: A Single-Institution Experience

Abstract: Background A novel coronavirus, SARS-CoV-2, was identified in Wuhan, China in late 2019. This virus rapidly spread around the world causing disease ranging from minimal symptoms to severe pneumonia, which was termed coronavirus disease (i.e., COVID). Postmortem examination is a valuable tool for studying the pathobiology of this new infection. Methods We report the clinicopathologic findings from 32 autopsy studies conducted on patients who died of COVID-19 including ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
157
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(190 citation statements)
references
References 37 publications
17
157
1
5
Order By: Relevance
“…In this regard, the high mortality of severe COVID-19 has been related to micro- or macrothrombosis, i.e. to endothelial cell injury ( Ackermann et al, 2020 ; Elsoukkary et al, 2020 ; Philipponnet et al, 2020 ). Although chloroquine was known to induce glycolipid deposits in lysosomes, the impact of this phenomenon on endothelial cell function had not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the high mortality of severe COVID-19 has been related to micro- or macrothrombosis, i.e. to endothelial cell injury ( Ackermann et al, 2020 ; Elsoukkary et al, 2020 ; Philipponnet et al, 2020 ). Although chloroquine was known to induce glycolipid deposits in lysosomes, the impact of this phenomenon on endothelial cell function had not been explored.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In another, the range was 1 to 58 days (median, 21 days). 23 A series of 30 “minimally invasive autopsies” included six patients with duration of illness listed as 63, 68, 75, 63, 71, and 82 days. 6 Not unexpectedly, the most striking degree of tissue damage has consistently been reported in the lungs.…”
mentioning
confidence: 99%
“…A large autopsy study of 32 cases by Salvatore et al [10] from the New York, one of the epicentres of the pandemic, showed the diversity of pathologic findings: besides diffuse alveolar damage, this cohort confirmed the increased frequency thromboembolisms in multiple organ systems. Furthermore, thanks to the diligent work-up of the cases, distinct histopathological patterns in lymph nodes and the liver were observed.…”
mentioning
confidence: 67%